(untitled) (International relations and international law Journal, 2016)
IN the twenty-first century Islamic factor it becomes an important part of international life. The relevance of the topic due to the increasing role of Islam in the modern world. In this regard, it is important the analysis of the mechanism of influence of the Islamic factor in the foreign policy of Arab States, its structure and the specifics of the article examines the nature, structure, content and main determinants of the Islamic factor, special attention is paid to the role of the Islamic factor in world politics. Examines the nature and structure of the mechanism of influence of the Islamic factor in the foreign policy of States, changes the content of the regional policy of the Arab countries under the influence of the Islamic factor in the end of XX – beginning of XXI century